2015
DOI: 10.1111/cdev.12378
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mexican Immigrant Parents’ Daily Workplace Discrimination on Child Behavior and Family Functioning

Abstract: This study investigated Mexican immigrant parents' reports of perceived workplace discrimination and their children's behavior, parents' moods, and parent-child interactions. Parents of one hundred and thirty-eight 3- to 5-year-old children were asked to complete one survey daily for 2 weeks (N = 1,592 days). On days when fathers perceived discrimination, fathers and mothers reported more externalizing child behaviors, and mothers reported fewer positive child behaviors. When mothers perceived discrimination, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
77
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(86 citation statements)
references
References 70 publications
6
77
1
2
Order By: Relevance
“…Several studies have demonstrated a link between parental perceived discrimination and child adjustment (Anderson et al., ; Ford et al., ; Gassman‐Pines, ; Gibbons et al., ). For example, Ford et al.…”
Section: Extending the Family Stress Model To The Context Of Parentalmentioning
confidence: 99%
“…Several studies have demonstrated a link between parental perceived discrimination and child adjustment (Anderson et al., ; Ford et al., ; Gassman‐Pines, ; Gibbons et al., ). For example, Ford et al.…”
Section: Extending the Family Stress Model To The Context Of Parentalmentioning
confidence: 99%
“…Keywords: Latino Families;Cultural Stress;Family Stress;Emotional Well-Being;Health Risk Behaviors Fam Proc 56:981-996, 2017 P arental stress is a normative experience that requires parents to balance the demands of their role as a parent (e.g., providing shelter and food) with their access to resources (e.g., employment and financial resources; Deater-Deckard, 2004). Studies have documented the negative effects of parental stress on their children's emotional and behavioral well-being (Conger, Conger, & Martin, 2010;Gassman-Pines, 2015;Leon, 2014;Tran, 2014). According to the Family Stress Model (FSM), parental stress may indirectly influence youth's emotional and health risk behaviors by compromising the emotional wellbeing of parents, their parenting behaviors, and family relationships (Conger et al, 2010).…”
mentioning
confidence: 99%
“…Once in the United States, parents may feel disillusioned and hopeless about their future (and that of their children) when they find themselves embedded in a social structure that they cannot change and experience cultural stressors (Perreira et al, 2006). Among Latino adults, acculturative stress (Hovey, 2000), discrimination (Lorenzo-Blanco & Cortina, 2013), and a negative context of reception (Schwartz et al, 2014) have been associated with elevated symptoms of depression and with compromised family functioning (Gassman-Pines, 2015;Trail, Goff, Bradbury, & Karney, 2012). Moreover, cross-sectional studies with ethnically diverse families have found parents' experiences with discrimination and acculturative stress to be directly associated with their children's internalizing and externalizing symptoms (Leon, 2014;Tran, 2014).…”
mentioning
confidence: 99%
“…Cultural stress may affect family functioning, and, in turn, the health of Latino youth and parents (e.g., Gassman-Pines, 2015;Lorenzo-Blanco, Meca, Unger, Romero, Gonzales-Backen, et al, 2016). Cultural stress refers to a constellation of interrelated but distinct factors that can contribute to the stress experience among Latino immigrant families, including discrimination, a negative context of reception, and acculturative or bicultural stress (Cano, Schwartz, Castillo, Romero, et al, 2015;Lorenzo-Blanco, Meca, Unger, Romero, Gonzales-Backen, et al, 2016).…”
Section: Cultural Stress Family Functioning Emotional Well-being Amentioning
confidence: 99%
“…In the United States, Latino immigrant adolescents and their parents can experience cultural stressors that result from navigating multiple cultural contexts, a negative context of reception, and experiencing discrimination (Cano, Schwartz, Castillo, Romero, et al, 2015;Gassman-Pines, 2015;Lorenzo-Blanco, Meca, Unger, Romero, Gonzales-Backen, et al, 2016;Schwartz et al, 2014Schwartz et al, , 2015, and these cultural stressors can negatively influence family functioning, emotional well-being, and health-risk behaviors among adolescents and parents. For example, in a daily diary study (Gassman-Pines, 2015), Mexican immigrant parents reported that, on days when they experienced workplace discrimination, they interacted less warmly and more aversely with their children, experienced lower emotional well-being, and reported more child internalizing and externalizing behaviors. In a longitudinal study with recent immigrant Latino families (Cano, Schwartz, Castillo, Unger, et al, 2015), positive family functioning predicted lower adolescent depressive symptoms and health-risk behaviors 6 months later, and family functioning was compromised in the presence of parent-child acculturation discrepancies.…”
mentioning
confidence: 99%